Status of ODC (Oxford System of Decimal Classification) in India - Mathur, N. K. (Indian Forester, 1981)
Documentation of forestry literature started as early as 1916 in India at the Forest Research Institute & Colleges, Dehra Dun. The classification system then followed was called Howard’s system after the name of Sir U.S. Howard who evolved it. It was followed for over two decades. In 1953 ODC was finally presented to the congress of IUFRO in Rome and was unanimously adopted with the recommendation that all its members follow suit. India was amongst the first countries to adopt ODC. The literature classified earlier under Howard’s system was kept separately for future reference and all the fresh literature being received was classified under ODC. Various state silviculturists were also directed to take up ODC. Since the start of this system at F.R.I. & Colleges, Dehr, Dun over 72.000 index cards and 5200 ODC ledger files have been built up. To facilitate summarization of these ledger files bibliography services were started and now bibliographies are being published annually by the Documentation and Bibliography Section of the Silviculture Branch at F.R.I. Seven bibliographies have already been published and a couple of them are under preparation. Selective dissemination of information on basis of the classified literature available in the section is also being done. With many new concepts in biomass studies, environmental pollution and energy crisis coming up after the evolution of ODC, there is now a strong need to update the oxford system of decimal classification. We must also think out ways and means to bring ODC on the computer line if we have to assure its future particularly so because ODC has served us so well over the last two decades. This paper briefly deals with the history development and present status of ODC in India.